Study on erosion and stability of the ecological slope - Tao, Hu; Lei, Shao-Wei; Gong, Li; Shi, Xi; Zhang, Meng-Meng; Yang, Guo-Qiang (Frontiers in Earth Science, 2023)
Rainfall is the main influencing factor causing slope erosion, landslide, and instability in loess; thus, it is vital to comprehend the process of rainfall erosion on various slope surfaces and water penetration inside the slope. In this paper, the loess sample is from Heifangtai in Gansu Province, and triaxial shear tests were conducted on loess with roots under varying water contents to evaluate the slope-reinforcing impact of roots. The slope surface erosion process was analyzed using a soil moisture sensor and matric suction meter to monitor the variation of matric suction in the middle slope and slope foot in response to varying precipitation levels.The numerical simulation approach is utilized to analyze the fluctuation of slope stability under the effect of varying rainfall intensities and humid heat, and the analytical solution of the safety factor is compared to the model solution. The results indicate that the shortest generation time for bare slope runoff is 6 minutes, whereas the greatest generation time for the Bermuda grass slope is 12 minutes; the shorter the period, the less water penetration and the simpler it is to reach the slope erosion stage. The slope's rise increases runoff velocity, strengthening water resistance on the slope surface. When the test slope is 30 degrees, the maximum mass of scouring sediment on the bare slope is 15.2 g from 24 to 36 minutes, compared to 14.7 g from 24 to 36 minutes when the test slope is 60 degrees. The amount of scouring reduces as the slope increases. The slope safety factor declined from 3.51 to 2.84 after 24 hours of heavy rain, and the loss rate accelerated as the rainfall intensity increased.